1999
DOI: 10.1080/00039899909602486
|View full text |Cite
|
Sign up to set email alerts
|

Determinants ofp,p'-Dichlorodiphenyldichloroethane (DDE) Concentration in Adipose Tissue in Women from Five European Cities

Abstract: To identify the determinants of p,p'-dichlorodiphenyldichloroethane (p,p'-DDE) in adipose tissue in subjects who participated in a cross-sectional study, we analyzed fatty acids, antioxidants, and p,p'-DDE in aspirates of adipose tissue of 328 postmenopausal women from 5 European countries. The overall mean of p,p'-DDE concentration was 1.66 microg/g of fatty acids (95% confidence interval = 1.46, 1.88). In a multiple-regression analysis, the main predictors of log10(p,p'DDE) were center of recruitment (p < .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 24 publications
1
7
1
Order By: Relevance
“…Despite a narrow age range, we showed a positive association of serum DDT with age consistent with other population-based studies (11)(12)(13). However, this age-DDT association was no longer present when birth year was controlled in the models (Table 2).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Despite a narrow age range, we showed a positive association of serum DDT with age consistent with other population-based studies (11)(12)(13). However, this age-DDT association was no longer present when birth year was controlled in the models (Table 2).…”
Section: Discussionsupporting
confidence: 77%
“…Although diet is a common source of DDT exposure for nonoccupationally exposed populations, specific dietary correlates of DDT/DDE have not been consistently shown (11,13). Most notably, basic health indicators, such as body mass index (BMI) and weight change, have been variously associated with serum DDT/DDE levels.…”
Section: Introductionmentioning
confidence: 99%
“…Four recent studies investigated predictors of organochlorine body burden in population-based samples recruited among elderly Germans [DeVoto et al, 1998], women from ®ve European cities [Sanz-Gallardo et al, 1999], nurses in the United States [Laden et al, 1999], and women from North Carolina [Schildkraut et al, 1999]. DeVoto et al [1998] reported that red meat intake was the strongest positive predictor of dieldrin, a-hexachlorocyclohexane (HCH), b-HCH, HCB, heptachlor epoxide, and DDT plasma levels among 297 elderly urban German residents.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their chemical structure, they are resistant to biodegradation and are therefore persistent in the human body (Johnson et al 2006). Chlorinated pesticides were also widely used in the United States and other countries until the 1970s and, like PCBs, are persistent and widely distributed in human tissues (Sanz-Gallardo et al 1999). …”
mentioning
confidence: 99%